METABOLISM OF GLIOFIBRILLARY ACIDIC PROTEIN IN PREGNANT WOMEN WITH POST-CONCUSSION SYNDROME - V. V. Simrok; I. V. Tsyganenko (Акушерство, гинекология и репродукция)
The aim: to evaluate the astroglial neurospecific protein – gliofibrillary acidic protein (GFAP) in the blood serum of pregnant women with post-concussion syndrome (PCS) resulted from a mild closed brain injury. The serum level of GFAP was earlier proposed to be used as a marker of the state of the blood-brain barrier (BBB) and a predictor of obstetric and perinatal complications.Materials and methods. To evaluate the permeability of the BBB and the integrity of astrocytes during pregnancy, we measured GFAP (using the enzyme immunoassay) in the sera of 93 women: 41 with PCS (main group), 31 somatically healthy pregnant women (comparison group), and 21 non-pregnant women of the reproductive age (control group).Results. In healthy pregnant women, the level of GFAP did not significantly differ from that in the non-pregnant women and did not exceed a threshold value of 4.0 ng/ml. In most of the pregnant women with PCS (70.73%), the GFAP values exceeded the threshold level starting from the first trimester and tended to increase subsequently, which was indicative of immunological sensitization.Conclusion. In the obstetric and neurological practice, pregnant women with PCS are recommend to be tested for their serum GFAP as a marker of immunological sensitization and a predictor of pregnancy and delivery complications as well as neurological deterioration.